2020
DOI: 10.1108/nfs-07-2019-0211
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant activity, extraction and application of psyllium mucilage in chocolate drink

Abstract: Purpose The purpose of this study is to extract psyllium mucilage and evaluate its antioxidant compounds (in the best extraction condition) and its application in a chocolate drink. Design/methodology/approach First, the extraction by ultrasonic bath was evaluated, followed by water bath extraction, and as there was no difference between the methods, a water bath experimental design was carried out to evaluate the best extraction conditions for psyllium mucilage, having response variables, yield and emulsion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 29 publications
0
5
2
1
Order By: Relevance
“…The optimal condition produced a maximum mucilage yield of 17.31 %, a water holding capacity of 11.48 g/g, and a minimum protein content of 1.75 % ( Table 3 ). Souza et al. (2020) reported higher mucilage yield for psyllium mucilage than the current study.…”
Section: Resultscontrasting
confidence: 79%
See 2 more Smart Citations
“…The optimal condition produced a maximum mucilage yield of 17.31 %, a water holding capacity of 11.48 g/g, and a minimum protein content of 1.75 % ( Table 3 ). Souza et al. (2020) reported higher mucilage yield for psyllium mucilage than the current study.…”
Section: Resultscontrasting
confidence: 79%
“…The optimal condition produced a maximum mucilage yield of 17.31%, a water holding capacity of 11.48 g/g, and a minimum protein content of 1.75 % (Table 3). Souza et al, (2020) reported higher mucilage yield for psyllium mucilage than the current study. However, it was found that (Hung et al, 2019) observed lower mucilage yield for basella alba mucilage compared to the present study.…”
Section: Optimization and Model Verificationcontrasting
confidence: 79%
See 1 more Smart Citation
“…Generally, all the extraction method of mucilage comprises of two successive procedures which are maceration and precipitation. Usually, the maceration extraction method of mucilage is simple and valuable, although the disadvantage of maceration is low efficiency and long extraction time [ 33 ]. This method consists of soaking the raw material in the chosen solvent at room temperature with regular agitation.…”
Section: Extraction Of Plant-derived Mucilagementioning
confidence: 99%
“…Research, Society and Development, v. 9, n. 10, e3469108094, 2020 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v9i10.8094 espessante de alimentos (Souza et al, 2020). Em outras pesquisas conduzidas por Raymundo et al 2014 psyllium aumentou a extensibilidade da massa crua e a firmeza dos discos pré-assados, sendo a massa com maior concentração de psyllium a mais bem aceita pelos consumidores, demonstrando que é viável uma produção em maior escala destinada tanto para públicos celíacos quanto para consumidores que optam por dietas isentas de glúten.…”
Section: Psylliumunclassified